Evaluation of DC-DC converter using renewable energy sources - Rajapandian B; Sundarrajan G.T (Institute of Advanced Engineering and Science, 2020)
This work analyses and evaluates the performance of renewable energy sources-based converters using Intelligent techniques. The objective of the research is to maintain the reliability of the converters such that it decreases the switching losses, high duty cycle and recycles the leakage energy. To accomplish the high output voltage gain converters are designed with different intelligent methods. Due to heavy demands, the cost of fossil fuel has gone up.so the need for the time is identifying and developing renewable energy sources along with developing new technologies for energy saving in renewable energy system to fight the issues plaguing the environment.